2007
DOI: 10.1158/1535-7163.mct-06-0423
|View full text |Cite
|
Sign up to set email alerts
|

Lapatinib induces apoptosis in trastuzumab-resistant breast cancer cells: effects on insulin-like growth factor I signaling

Abstract: The majority of breast cancer patients who achieve an initial therapeutic response to the HER2-targeted antibody trastuzumab will show disease progression within 1 year. Thus, the identification of novel agents that effectively inhibit survival of cancer cells that have progressed on trastuzumab is critical. In the current study, we show that the dual epidermal growth factor receptor (EGFR)/human EGFR-2 (HER2) kinase inhibitor lapatinib induces apoptosis in trastuzumab-resistant cells derived from the HER2-ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
160
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(169 citation statements)
references
References 20 publications
6
160
2
1
Order By: Relevance
“…Lapatinib response may be independent of PTEN, PIK3CA and IGF1R, as supported by lapatinib responses observed in these studies and demonstrated in preclinical studies (Nahta et al, 2007;Xia et al, 2007). Patients with HER2-positive tumours having PIK3CA amino acid changes derived benefit from lapatinib.…”
Section: Discussionsupporting
confidence: 55%
“…Lapatinib response may be independent of PTEN, PIK3CA and IGF1R, as supported by lapatinib responses observed in these studies and demonstrated in preclinical studies (Nahta et al, 2007;Xia et al, 2007). Patients with HER2-positive tumours having PIK3CA amino acid changes derived benefit from lapatinib.…”
Section: Discussionsupporting
confidence: 55%
“…Homodimerization and heterodimerization among members of the ErbB family of receptors are known to occur, thus making therapy directed against a single receptor ineffective at times (40). Agents that target multiple HER receptors are thus desirable; the dual kinase receptor lapatinib targets both EGFR and HER-2, and thus has been found to be more effective in the treatment of angiogenesis in metastatic cancers (41). Similarly, NVP-AEE788, a dual tyrosine kinase activity inhibitor of EGFR and ErbB-2, was more efficient at treating biliary tract cancer than were EGFR inhibitors alone (42).…”
Section: Discussionmentioning
confidence: 99%
“…86 Recently, studies have suggested that the dual HER2/EGFR tyrosine kinase inhibitor lapatinib targeted against both EGFR and HER2 inhibited the growth of HER2-overexpression breast cancer cells in patients receiving prolonged treatment with trastuzumab, 87 and inhibited insulin-like growth factor I (IGF-I) signaling in resistant cells. 88 This type of approach has potential in HER2-overexpressing breast cancers, as well as in trastuzumab-refractory patients, and constitutes a novel strategy that cotargets the IGF-I receptor and HER2 pathways. Along the same line, novel IGF-IR targeted agents and PI3K inhibitors are currently studied for potential use in trastuzumab refractory patients.…”
Section: Resultsmentioning
confidence: 99%